ANALISIS PENGARUH PENGUNGKAPAN TANGGUNG JAWAB SOSIAL DAN TATA KELOLA PERUSAHAAN PADA MANAJEMEN LABA (Studi Empiris pada Perusahaan yang Terdaftar pada BEI Tahun 2018) - Valeria Natasha; Agus Purwanto (Diponegoro Journal of Accounting, 2020)
This research aims to examine the effect of corporate social responsibility disclosure and corporate governance on earnings management in non-financial companies listed on the Indonesia Stock Exchange in 2018. The corporate governance variables used are managerial ownership, audit committee, and independent of board commissioners. The theory used in this study is agency theory.The data used in this research are secondary data using a purposive sampling method as a method of determining the sample, this research obtained 247 companies as a sample. This study used multiple linear regression analysis to test the hypotheses.The results of this research  successfully demonstrated that disclosure of corporate social responsibility, managerial ownership, and independent of board commissioners has a significant negative effect on earnings management. However, this study did not find a relationship between the audit committee and earnings management.